Volunteer Selection Model in a Community-Based Qur’anic Learning Center: A Case Study of Abata Movement Indonesia: Model Seleksi Relawan pada Taman Pendidikan Al Qur’an Berbasis Komunitas: Studi Kasus pada Abata Movement Indonesia - Warohma Iftitiyani; Muhammad Munadi (RADIANT: Journal of Applied, Social, and Education Studies, 2026)
The Qur’anic Learning Center (TPQ) plays an important role in community-based character education, but limitations in human resources and funding make the role of volunteers crucial. The mismatch between institutional needs and volunteer capacity highlights the importance of clear criteria for determining volunteers. This study uses a qualitative approach with a case study at TPQ Abata Movement Indonesia. Data were collected through interviews, observation, and document analysis. The results show that Abata Movement implements volunteer recruitment systematically with three main criteria: competence, spirituality, and commitment. These three criteria play an important role in maintaining the quality, sustainability, and effectiveness of community-based Qur’anic learning programs. This study is expected to serve as a reference for developing volunteer selection and management models in community-based Qur’anic learning institutions.